Irradiation processing to modify HDPE molecular architecture: Correlation with irradiation conditions and polymer grade. (June 2022) - Moradkhani, Elham; Entezam, Mehdi; Ahmadi, Mostafa; Khonakdar, Hossein Ali; Ruckdäschel, Holger; Altstaedt, Volker
Abstract: Irradiation process is an effective technique to modify the molecular architecture, and therefore, the processability and thermo-mechanical properties of polyolefins. In this study, the utility of irradiation dose and atmosphere, heat treatment of the raw material prior to irradiation and the polymer grade, as the most important parameters to influence the irradiation performance in terms of modifying the molecular characteristics, rheological, and thermo-mechanical properties of high-density polyethylene are comprehensively investigated. According to the SEC analysis and linear viscoelastic rheology results, long chain branch formation is predominant at doses below 25 kGy, which is strongly influenced by the polymer grade but not by the heat treatment. Rheological analyses also suggest a star like molecular architecture for branched HDPE chains. Unexpectedly, Ziegler-Natta catalyzed HDPE grades were found to be branched significantly more than Philips catalyzed ones, which highlights the dominance of chain mobility factor over the presence of unsaturated bonds. The extent of crystallinity and tensile mechanical properties also change upon irradiation, in agreement with the extent of molecular architecture modification. These results provide a useful guideline to control the extent of the irradiation induced LCB in HDPE. Graphical Abstract: ga1 Highlights: Irradiation at low doses create long chain branch in high-density polyethylene. The reduced van Gurp-Palmen plot suggests the formation of star-like chains. Polyethylene grade as well as irradiation dose significantly influences irradiation performance. Preheating treatment of raw material have no effect on irradiation performance. Branched high-density polyethylene show a significant increase of tensile strength. Irradiation cause an obvious decrease in the extent of crystallization.